Modern Portfolio Theory and Investment Analysis / Third Edition - Elton Edwin J; Gruber Martin J (John Wiley And Sons, Inc, 1987)
Introduction, Portfolio Analysis, Mean Variance Portfolio Theory, The Characteristics of the Opportunity Set Under Risk, Delineating Efficient Portfolios, Techniques for Calculating the Efficient Frontier, Simplifying the Portfolio Selection Process, The Correlation Structure of Security Returns: The Single Index Model, The Correlation Structure of Security Returns: Multi-index Models and Grouping Technique, Simple Techniques for Determining the Efficient Frontier, Selecting the Optimum Portfolio, Utility Analysis, Other Portfolio Selection Models, Widening the Selection Universe, International Diversification, Models of Equilibrium in the Capital Markets, The Standard Capital Asset Pricing Model, Nonstandard Forms of Capital Asset Pricing Models, Empirical Tests of Equilibrium Models, Security Analysis and Portfolio Theory, Efficient Markets, The Valuation Process, Earning Estimation, Interest Rate Theory and the Pricing of Bonds, Evaluating the Investment Process, Index.